A Set of Professional Tools to Support the Design and Evaluation of Real-Time Payment Systems and Emergent Users - Teran, Luciano Arruda; Melo, Giselle Lorrane Nobre; Silva, Ingrid Moreira Miranda da; Salles, Rafael Barbosa de; Rocha, Thayssa Águila da; Mota, Marcelle Pereira (Journal on Interactive Systems, 2024)
The popularization of the smartphone has generated new financial technology opportunities for our society. In Brazil, with the emergence of Pix in 2020, several people are migrating to this tool to obtain new payment and income acquisition forms. However, the social characteristics of people facing longitudinal barriers, access to formal education, and computational systems must be considered to improve digital and financial access. We aim to provide a web platform, called Inclue Platform to help software developers design and evaluate their real-time payment systems promoting emergent user inclusion. The research combined a set of methodological procedures: literature review, questionnaires, interviews, two case studies and a viability test. Software development professionals, a riverside community, and residents of an Amazonian city engaged in this study. The communicability assessment method was used in the case studies. The Include Platform viability test results suggest that it can be an effective support tool for software development professionals, although its content could still be improved.